An Ambivalent Relationship: Thomas Caddy, the Drapers' Association and the Sydney Trades and Labor Council's Forgotten Cooperation over Early Closing. (1st May 2016) - Bastian, Peter; Quayle, Victor
Abstract : Attempts by retail workers to limit their hours of employment through campaigns for the early closing of shops have received only limited attention. Yet, Sydney's drapery community played a longstanding and prominent role in this movement. In the 1880s, Thomas Caddy helped foster an alliance, now completely forgotten, between the Drapers' Association and the Sydney Trades and Labor Council to campaign for early closing by moral suasion. These moves ended in failure and revealed the problems associated with using moral suasion tactics, the fluidity of early worker affiliations, the strengths and limitations of early peak union councils and the changing status of workers within the drapery trade.